Systematic review on the appreciation of Afro-Brazilian culture in rural schools - Francislene Alves Bezerra; Jonas Carvalho e Silva; Rosane Balsan (Universidade Federal do Norte do Tocantins, 2024)
This review aims to analyze the scientific production on the application of Federal Law n. 10,639/03 in rural schools in Brazil. The survey followed the protocol of Main Items to Report Systematic Reviews and Meta-analyses- PRISMA, and was carried out in the databases of the Brazilian Digital Library of Theses and Dissertations (CAPES), Online Scientific Electronic Library- Scielo, Brazilian Association of Black Researchers (ABPN), Web of Science, digital collection of the University of Dortmund and the Institutional Repository of the Federal University of Tocantins (UFT). Nineteen research reports were included, which, after applying the inclusion and exclusion criteria, were categorized into 3 groups: research on education for ethnic-racial relations in rural schools; the school and the struggle for land; and culture and identity of the peasant people. The year of publication, author, title, name of the program/university and periodical, type (dissertation, thesis or periodical), indicated keywords, objectives, method and collection instruments, participants, main results and conclusions/recommendations. The results indicated the predominance of qualitative methods, through the use of semi-structured interviews, informal interviews, document analysis, ethnography, case study, field diary, participant observation, literature review, conversation circle, among others. These strategies make it possible to know the experiences of the subjects involved in educational practices for the implementation of the Law. There was a small number of works found, in the selected databases, on the theme that addresses the applicability of the Law in rural schools. It is recommended the development of researches that evaluate the effectiveness of the Law, especially with large samples and with quantitative designs.